2015
DOI: 10.1177/2347631115610221
|View full text |Cite
|
Sign up to set email alerts
|

Students on Move

Abstract: In recent years, the overall context of global mobility has significantly changed, so has the strategies to attract international students. What we observe now is the changes in strategies and the emergence of new host countries and increased opportunities for studying abroad. In an intense competitive environment of global higher education market, host countries are targeting students from Asian origin in general and Indian students in particular. Increasing competition for international students has caused c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 33 publications
3
15
0
1
Order By: Relevance
“…Respondents recommend this university to those prospective students who have average ability and limited budget. These findings are consistent with Wadhwa (2016) who found that tuition and institution fees, availability of scholarships and financial aid, and quality of faculty influenced students to choose a particular host institution. Lee (2014) also found that cost issues most influenced international students' decision-making processes whereas recommendation from others was the least important.…”
Section: Alternative Evaluationsupporting
confidence: 89%
See 2 more Smart Citations
“…Respondents recommend this university to those prospective students who have average ability and limited budget. These findings are consistent with Wadhwa (2016) who found that tuition and institution fees, availability of scholarships and financial aid, and quality of faculty influenced students to choose a particular host institution. Lee (2014) also found that cost issues most influenced international students' decision-making processes whereas recommendation from others was the least important.…”
Section: Alternative Evaluationsupporting
confidence: 89%
“…Prospective students trust that the information coming from personal sources (friends, family) or public sources (student associations, university rankings) are independent and unbiased. This supports the findings of Rafi (2018) and Wadhwa (2016). They argue that friends and relatives are the primary sources of information used by prospective students followed by institutional coaching centers, the Internet, agents and education fairs.…”
Section: Information Searchsupporting
confidence: 83%
See 1 more Smart Citation
“…Location gives impression of institute's site and its connectivity from hometown, while locality refers to culture, amenities, and facilities available in surrounding place wherein the institution is located. Overall, it is credited with suitability, vicinity, attractiveness, accessibility, cost-effectiveness, safety and security (Hannagan, 1992;Kotler & Fox, 1995) Image and reputation Image and reputation in public minds plays a signi cant role in differentiating institutions (Imenda et al, 2004) and is measured as one of the topmost characteristics in uencing institution choice (Briggs, 2006) (Wadhwa, 2016). It is composed of a spectrum of small reputes, such as academic and nonacademic characteristics belonging to institutions (Lafuente-Ruiz- de-Sabando et al, 2018).…”
Section: Location and Localitymentioning
confidence: 99%
“…Students have the luxury to choose based on the comparison and reviews made by the alumni. Wadhwa (2016)and Mohamad and Hussein (2018). Meyer (2018) also highlighted that the decision-making by students will be based on their purpose and intention.…”
Section: Students' Decision Makingmentioning
confidence: 99%